EFEKTIVITAS MEDIA VIDEO TUTORIAL DALAM KETERAMPILAN VOKASIONAL MEMBUAT BUNGA DARI KANTONG PLASTIK KRESEK BERWARNA PUTIH DI SLBN 1 PADANG SIDEMPUAN - Hasibuan, Siti Ertina; ., Armaini (Inspiratif Pendidikan, 2021)
This study aims to prove the effectiveness of video tutorial media in making flowers from white crackle bags for deaf children in class X at SLBN Padang Sidempuan. This research is based on the problems found in SLB 1 Padang Sidempuan class X in Tuanrungu which consists of five students, generally deaf children have been taught several skills but the skill of making flowers from plastic bags has never been taught to children. This study uses a type of research, namely the experimental method. The method used to determine whether the media model with video tutorials could be effectively used in making flowers from white plastic bags. The subjects of this study were deaf children in class X at SLBN Padang Sidempuan The results of this study were an increase in children's ability to make flowers from plastic bags after being given treatment using video tutorial media. The results of the comparison of the pretest and posttest percentages showed an increasing ratio of the ability to make flowers from plastic plastic bags for deaf children of class X B at SLB Negeri 1 Padang Sidempuan after being treated using video tutorials. Research with a direct learning model conducted by researchers with the aim of proving that video tutorial media can be effective in flower making skills can be seen by comparing the pre-test and post-test scores and can be proven through the Wilcoxon Sign Rank Test where Zhitung = -2.023b and Asymp. Sig (2-tailed) = .043, meaning Zhitung> Asymp.Sig. (2-tailed) thus Ho is rejected and Ha is accepted.